Stress vulnerability promotes an alcohol‐prone phenotype in a preclinical model of sustained depression. (18th December 2018) - Riga, Danai; Schmitz, Leanne J.M.; van Mourik, Yvar; Hoogendijk, Witte J.G.; De Vries, Taco J.; Smit, August B.; Spijker, Sabine
Abstract: Major depression and alcohol‐related disorders frequently co‐occur. Depression severity weighs on the magnitude and persistence of comorbid alcohol use disorder (AUD), with severe implications for disease prognosis. Here, we investigated whether depression vulnerability drives propensity to AUD at the preclinical level. We used the social defeat–induced persistent stress (SDPS) model of chronic depression in combination with operant alcohol self‐administration (SA). Male Wistar rats were subjected to social defeat (five episodes) and prolonged social isolation ( 12 weeks) and subsequently classified as SDPS‐prone or SDPS‐resilient based on their affective and cognitive performance. Using an operant alcohol SA paradigm, acquisition, motivation, extinction, and cue‐induced reinstatement of alcohol seeking were examined in the two subpopulations. SDPS‐prone animals showed increased alcohol SA, heightened motivation to acquire alcohol, persistent alcohol seeking despite alcohol unavailability, signs of extinction resistance, and increased cue‐induced relapse; the latter could be blocked by the α2 adrenoreceptor agonist guanfacine. In SDPS‐resilient rats, prior exposure to social defeat increased alcohol SA without affecting any other measures of alcohol seeking and alcohol taking. Our data revealed that depression proneness confers vulnerability to alcohol, emulating patterns of alcohol dependence seen in human addicts, and that depression resilience to a large extent protects from the development of AUD‐like phenotypes. Furthermore, our data suggest that stress exposure alone, independently of depressive symptoms, alters alcohol intake in the long‐term. Abstract : Stress contributes to depressive and addictive pathologies alike. We examined how individual differences in responsivity to stress affect patterns of alcohol seeking and alcohol taking in a preclinical model of chronic depression, the social defeat‐induced persistent stress (SDPS) paradigm. Our findings indicated that stress vulnerability, manifested in long‐lasting affective and cognitive deficits, triggers an alcohol‐prone phenotype that mirrors alcohol dependence as seen in humans. Accordingly, stress resilience, which inhibits the development of chronic depression, protects from the emergence of addiction‐like manifestations.